Siddha medicine practitioners and their knowledge, attitude and practice about tuberculosis patients: an observational study in Tamil Nadu, India - Gnanasoundran, Vanitha; Dhandayuthapani, Thanigaivelan (International Journal of Research in Medical Sciences, 2019)
Background: Siddha medicine is one of the commonest alternative medicine among AYUSH (ayurveda, yoga and naturopathy, unani, siddha, homeopathy) medicine practiced in Tamilnadu, one of the southern states of India, where it originated originally. To assess the knowledge, attitude and practice of siddha medicine practitioners towards Tuberculosis, a leading infectious disease-causing increased mortality and morbidity in the country where world’s one fifth of the diseased patients of tuberculosis live and how these alternative medicine practitioners are helping the national programme of eradicating TB in 2025 with their practice. Methods: A Questionnaire was prepared regarding the symptoms, investigations, treatment of TB and about its knowledge of recent trend. One siddha medicine practitioner was randomly selected from the 32 districts of the state from the registry, interviewed and assessed. Results: Out of the 32 siddha practitioners interviewed, 96% referred the tuberculosis patients to the nearby government hospitals for the antituberculous treatment but with the supportive siddha medicine. Regarding the awareness or update of the recent change in the TB regime and the national programme, only 10% of the siddha medicine practitioners were sensitised that too only those working in government hospitals. Conclusions: Siddha medicine practitioners mostly referred the tuberculosis patients, but they are insisting on the supportive role of siddha medicine along with the standard anti tuberculous drugs for the general improvement of the patient. Also, the sensitisation programmes for these Siddha practitioners should be initiated for the better outcome of the RNTCP (Revised National Tuberculosis Control Programme), especially in the private setup.